2017
DOI: 10.2196/preprints.9211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-Scale Dissemination of Internet-Based Cognitive Behavioral Therapy for Youth Anxiety: Feasibility and Acceptability Study (Preprint)

Abstract: 1 Open-access, online CBT for youth anxiety Abstract Background: Internet-based CBT (iCBT) for child and adolescent anxiety has demonstrated

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Benefits are not just in terms of clinical improvement but also in terms of cost, availability, accessibility, and time. 18 A systematic review of smartphone apps for mental illnesses showed an increased usage of these apps for common mental health illness with decreased need for physical contact with the therapist or psychologist, thereby allowing flexibility and cost-effectiveness in treatment. 19 Field studies of smartphone apps that provided teleconsult followed by promotional messages were found useful for the management of depression and anxiety.…”
Section: Ehealth Interventionsmentioning
confidence: 99%
“…Benefits are not just in terms of clinical improvement but also in terms of cost, availability, accessibility, and time. 18 A systematic review of smartphone apps for mental illnesses showed an increased usage of these apps for common mental health illness with decreased need for physical contact with the therapist or psychologist, thereby allowing flexibility and cost-effectiveness in treatment. 19 Field studies of smartphone apps that provided teleconsult followed by promotional messages were found useful for the management of depression and anxiety.…”
Section: Ehealth Interventionsmentioning
confidence: 99%